Improving the Productivity and Energy Efficiency by a Heat Treatment Method Applied to Aluminum Forged Parts - Surmen, Omer; Zeytin, Sakin; Tarakci, Mehmet; Gencer, Yucel (European Scientific Journal, ESJ, 2018)
In industrial applications, hot forging of AA6082 alloy is carried at 480°C. After the hot forging operation parts are cooled down to room temperature and heated again up to 540°C for solution heat treatment and artificially aged. Heating-cooling-heating cycles leads to energy and time loss in production, and have long-termenvironmental and economic impacts. Mass production of aluminum parts for applications in various industries (automotive, aerospace etc.) requires a process with higher productivity. The aim of this study was to provide time and energy efficiency by combining hot forging and solution treatment processes into a single operation. AA6082 billets were forged at 540°C for 7.5, 15 and 30 minutes in order to achieve simultaneous solution treatment. Billets were then water quenched and artificially aged. Mechanical properties (hardness, tensile strength) as well as microstructure of samples were investigated. Required mechanical properties were achieved on the samples forged and treated at 540°C for 15 and 30 minutes.